Ecophysiological Traits of Invasive C3 Species Calotropis procera to Maintain High Photosynthetic Performance Under High VPD and Low Soil Water Balance in Semi-Arid and Seacoast Zones - Rivas, Rebeca; Barros, Vanessa; Falcão, Hiram; Frosi, Gabriella; Arruda, Emília; Santos, Mauro (Frontiers in Plant Science, 2020)
Evergreen C3 plant Calotropis procera is native to arid environments. Thus, it grows under high vapor pressure deficit, light intensity and severe drought season. We measured several ecophysiological traits in C. procera under semiarid and seacoast environment to assess the attributes that support its photosynthetic performance in these contrasting conditions. Gas exchange analysis, primary metabolism content, nutrients, antioxidant system and leaf anatomy traits were measured under field conditions. In semiarid, C. procera was exposed to prolonged drought season during the two years of study with negative soil water balance. Calotropis procera plants were exposed to positive soil water balance only under rainy season at seacoast environment. The leaves of C. procera showed the same photosynthetic rate under high or low VPD even in dry season with negative soil water balance. Photosynthetic pigments, leaf sugars content and activity of antioxidant enzymes were increased in both places under dry season. However, the anatomical adjustments were contrasting, while in semiarid mesophyll thickness increased under driest year, in seacoast cuticle thickness and trichomes density was increased. The ability to keep photosynthetic performance through the seasons would be supported by new leaves with different morpho-anatomical traits with contrasting changes between semiarid and seacoast environments. Furthermore, our results suggest that efficient antioxidative system and leaf sugar dynamics can contribute to protect the photosynthetic machinery even under severe drought season.